Phosphorylation and an ATP-dependent process increase the dynamic exchange of H1 in chromatin - Dou, Yali (The Rockefeller University Press, 2002)
In Tetrahymena cells, phosphorylation of linker histone H1 regulates transcription of specific genes. Phosphorylation acts by creating a localized negative charge patch and phenocopies the loss of H1 from chromatin, suggesting that it affects transcription by regulating the dissociation of H1 from chromatin. To test this hypothesis, we used FRAP of GFP-tagged H1 to analyze the effects of mutations that either eliminate or mimic phosphorylation on the binding of H1 to chromatin both in vivo and in vitro. We demonstrate that phosphorylation can increase the rate of dissociation of H1 from chromatin, providing a mechanism by which it can affect H1 function in vivo. We also demonstrate a previously undescribed ATP-dependent process that has a global effect on the dynamic binding of linker histone to chromatin.